2013
DOI: 10.1310/hpj4811-931
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions: A Retrospective Review of Hospitalized Patients at a State Psychiatric Hospital

Abstract: ADRs were most commonly associated with mood stabilizers and antipsychotics, and pADRs were common. There is an opportunity to provide education to medical staff on therapeutic drug monitoring and drug-drug interactions for these classes, particularly lithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Most of the other studies like Luppa CA et al Kuruvilla A et al and Rothschild J m el al have reported Antipsychotic is most common drug class for ADRs. 7,8,18 From patient"s data, our study was observed that risperidone 19 (46.34%), haloperidol 13 (31.7%), lithium 12 (100%) and imipramine 8 (57.14%) were most frequently suspected drugs in group A while risperidone 10 (45.45%), trifluoperazine 4 (18.18%) and quetiapine 4 (18.18%) were the common causes of ADRs requiring hospitalisation in group B.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Most of the other studies like Luppa CA et al Kuruvilla A et al and Rothschild J m el al have reported Antipsychotic is most common drug class for ADRs. 7,8,18 From patient"s data, our study was observed that risperidone 19 (46.34%), haloperidol 13 (31.7%), lithium 12 (100%) and imipramine 8 (57.14%) were most frequently suspected drugs in group A while risperidone 10 (45.45%), trifluoperazine 4 (18.18%) and quetiapine 4 (18.18%) were the common causes of ADRs requiring hospitalisation in group B.…”
mentioning
confidence: 77%
“…Targeting high-risk medications that have been identified through analysis could have a significant impact on reducing preventable ADRs. 8 The present study was carried out to study the incidence and the pattern of ADRs taking place in psychiatry units of tertiary care, teaching hospital, Jamnagar over a period of four year. It was thought that this hospital data based monitoring of ADRs can shed light on their extensiveness and pattern of occurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning a study conducted at a state psychiatric hospital in United States, which underlines the role of clinical pharmacists; where pharmacists also actively review all laboratory results and medication orders for indications that an ADR has occurred and help data entry into an internal online computer database. 17 Yet another study in UAE also fosters the role of clinical pharmacist. 8 Building up of a database with combined efforts of pharmacologists and psychiatrists has been suggested by previous articles.…”
Section: Discussionmentioning
confidence: 99%
“…It can be done by the data use of frequency, severity, probability and preventability. After getting all the information of high-risk drugs through analysis may have significant impact on reducing the ADRs 9,10. Hence, an attempt has been made in this article exhibit an updated analysis of ADRs which are caused by antipsychotics drug and how to manage the ADRs in general outlook and what are the future outcomes in the management of adverse drug reaction 11 .…”
Section: Obsessive Compulsive Disorder (Ocd)mentioning
confidence: 99%